Spiritual coping "tri hita karana" and depression prevention behavior among the elderly during the Covid-19 pandemic - I. Wayan Suardana; Ah Yusuf; Rachmat Hargono; I. Gede Juanamasta; Ketut Sudiantara; I. Ketut Gama; I. Wayan Mustika (PAGEPress Publications, 2024)
The elderly commonly struggle with mental health issues, especially depression. Spiritual coping is one of the factors that might prevent depression. The aim of this study is to investigate cultural involvement in spiritual coping to depression prevention among the Balinese elderly. From January to March 2021, this study was carried out on 273 elderly members of the Integrated Primary Public Health service in seven districts in Gianyar, Bali. The study used a cluster random sampling method to collect data and focused on quantitative measurements related to participant characteristics, depression prevention, and spiritual coping. The investigation into spiritual coping was based on the tri hita karana, a concept from Balinese philosophy. Bivariate analysis was used to assess the relationship between spiritual coping and depression prevention behaviour. The study comprised 146 male and 127 female participants aged between 65 and 79 years old. Among all participants, 190 (69,6%) were diagnosed with mild to moderate depression, while 83 (30,4%) with moderate to severe depression. However, for the majority, depression prevention was good 163 (59,7%), the rest was moderate 103 (37,7%), and poor 7 (2,6%). Tri hita karana spiritual coping for the majority was good 17 (53,8%). Spiritual coping has a strong correlation with depression prevention (r=0.230). Thus, spiritual coping has a strong correlation with depression prevention among the Balinese elderly. It can be concluded that the implementation of tri hita karana becomes a potent spiritual coping enhance depression prevention. Indigenous philosophy embedded in daily life supports social capital in dealing with stress.